How young people in Finland respond to information about the origin of food products: The role of value orientations and product type - Tommi Kumpulainen; Annukka Vainio; Mari Sandell; Anu Hopia (Elsevier, 2022)
The aim of this study was to explore the effect of personal values and product type in an experimental study/survey concerning food origins. Two studies were conducted among young consumers (N = 1491) using three different types of products (vegetables, bread, and meat) and an experimental design where information about the food origin varied (neutral, domestic, local). The origin of the food had a positive effect on the product experience and food choices. Value orientations had an effect on the product experience and the likelihood of choosing the product, and this effect was dependent on the product type. More specifically, a Self-Transcendence orientation was positively associated with the product experience in the context of vegetables and a Conservation orientation was positively associated with the product experience in the context of meat, however, the value orientations showed no effect in the context of bread. Individuals regarding Self-Transcendence as important, especially valued a local origin in the context of vegetables and meat. The findings regarding a Conservation orientation were less consistent. These findings indicate that knowing the origin adds some value to the product for young people. Even if the product is not necessarily in line with an individual’s values, the origin may in fact exceed the effect of the product type. The study provides further knowledge about the underlying factors explaining consumer choices on a personal level, especially when extrinsic information cues about food origin are available.